HUBUNGAN KARAKTERISTIK PETUGA BACA DENGAN FREKWENSI KESALAHAN BACA STAND KWH METER PELANGGAN - Adam, Muhammad (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Electricity in an equipment to increase human life value. the level og electricity energy onsumption reflects the level of costumer welfare. Costumer welfare should be in balance betweenthe right and the obligation to pay the electicity energy used monthly.